SPATIAL REGENERATION OF MUSLIM BURIAL PRACTICES IN THE METROPOLITAN AREAS OF KUALA LUMPUR AND JAKARTA - Mohamed Afla, Mohamad Reza (PLANNING MALAYSIA, 2018)
This article focuses on the subject of burial practices which are performed by the Muslim population and the management at public cemeteries within the metropolitan areas of Kuala Lumpur and Jakarta. This research examines specifically, the conventional way of burial practice by the majority of the Muslim population. Unlike other major religions in Southeast Asia which are more open and flexible in the disposal of corpses, full body burial is mandatory in Islam. In response to the escalating issue of lack of space and land shortage for Muslim cemetery, local authorities of the two metropolitan areas have identified alternatives and solutions in handling these alarming situations. This research has recognised factors that lead to these problems, as well as discussing available methods to overcome these issues. The finding exhibits Muslim cemetery’s layout to be problematic due to abundance of burial practices accumulated by patrons which led to disorganisation of space and claustrophobia. This article concludes by providing proposals and design guidelines at the terrain level, together with recommendations that emphasise the long-term usage of the grave plots.